THE INTENSITY OF ESTRUS OF SILENT HEAT BALI CATTLE - Agustina, I Putu Sudana; Laksmi, Desak Nyoman Dewi Indira; Trilaksana, I Gusti Ngurah Bagus; Budiasa, Made Kota (Buletin Veteriner Udayana, 2021)
This research was conducted to determine the follicle diameter and estrous intensity of bali cattle that ever had a silent heat in the livestock group of Integrated Farming Systems (SIPADU) in Mengwi Subdistrict Badung Regency, Bali Province, which was implemented in September – Oktober 2019. Bali cattle are grouped into 2 (two) groups; first, the Bali cattle, whichever had silent heat. Second, the Bali cattle whichever had estrous. The results showed the estrous intensity of bali cattle with silent heat showed significant differences (p < 0.05), it is vulva temperature (37,68 + 0,32ºC), vulva diameter (27.64 + 4.28 mm), vulva color (pink, invisible peripheral vessels ) and vulva mucus (no mucus until there was little mucus ). Compared to the group of bali cattle which had estrus, it is vulva temperature (37.96 + 0.51°C), vulva diameter (31,19 + 5,66 mm), vulva color (bright red to dark red and peripheral vessels branching clearly) and vulva mucus (viscous, transparent hang out). The results of the study concluded that there was a difference between the estrus intensity in bali cattle that had silent heat and bali cattle that showed true estrus.